2020
DOI: 10.1002/1878-0261.12828
|View full text |Cite
|
Sign up to set email alerts
|

TGFBI modulates tumour hypoxia and promotes breast cancer metastasis

Abstract: Breast cancer metastasis is a complex process that depends on intrinsic characteristics of metastatic stem cells, but also on the particular microenvironment that supports their growth and modulates the plasticity of the system. In search for microenvironmental factors supporting cancer stem cell (CSC) growth and tumour progression to metastasis, we here investigated the role of the matricellular protein Transforming Growth Factor Beta Induced (TGFBI) in breast cancer. We crossed the MMTV-PyMT model of mammary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 66 publications
0
33
0
Order By: Relevance
“…We showed that this matricellular protein has immunosuppressive properties in an autoimmune context [ 170 ]. Also, in their recent study Fico and Santamaria-Martínez demonstrated that βig-h3 promotes breast cancer metastasis and plays an important role in tumor angiogenesis [ 171 ]. Moreover, employing a KO model of βig-h3 as well as in silico analysis of human breast cancer samples, they showed that βig-h3 overexpression is positively linked with tumor hypoxia and M2 macrophages but negatively associated with CD8+ T cell infiltration [ 171 ].…”
Section: Immune Regulation By Ecm Proteins In Digestive Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…We showed that this matricellular protein has immunosuppressive properties in an autoimmune context [ 170 ]. Also, in their recent study Fico and Santamaria-Martínez demonstrated that βig-h3 promotes breast cancer metastasis and plays an important role in tumor angiogenesis [ 171 ]. Moreover, employing a KO model of βig-h3 as well as in silico analysis of human breast cancer samples, they showed that βig-h3 overexpression is positively linked with tumor hypoxia and M2 macrophages but negatively associated with CD8+ T cell infiltration [ 171 ].…”
Section: Immune Regulation By Ecm Proteins In Digestive Cancersmentioning
confidence: 99%
“…Also, in their recent study Fico and Santamaria-Martínez demonstrated that βig-h3 promotes breast cancer metastasis and plays an important role in tumor angiogenesis [ 171 ]. Moreover, employing a KO model of βig-h3 as well as in silico analysis of human breast cancer samples, they showed that βig-h3 overexpression is positively linked with tumor hypoxia and M2 macrophages but negatively associated with CD8+ T cell infiltration [ 171 ]. In fibrosis and wound healing, macrophage-derived βig-h3 that is released after the uptake of apoptotic cells is considered to control collagen turnover as shown in a study from Nacu et al [ 172 ].…”
Section: Immune Regulation By Ecm Proteins In Digestive Cancersmentioning
confidence: 99%
“…Bone tissue is one of the most common sites for metastases in patients with advanced breast cancer, and the metastatic ratio is much higher than that of the liver, lung, and kidney ( Park et al, 2020 ; Zhang D. et al, 2020 ). Breast cancer metastasis to bones not only affects patient quality of life but also results in anemia, fractures, paraplegia, hypercalcemia, pain, cachexia, and increased mortality ( Fico and Santamaria-Martinez, 2020 ). When breast tumors metastasize to bone, the balance between osteoblasts and osteoclasts is damaged.…”
Section: Extracellular Vesicles and Bone Metastasismentioning
confidence: 99%
“…As happens with other components of the TME, certain components of the ECM have been proposed to have prognostic value in breast cancer. These include hyaluronan [ 166 , 167 ], asporin [ 168 , 169 ], syndecans [ 170 , 171 ], versican [ 172 , 173 ], collagens [ 174 , 175 ], fibronectin [ 174 , 176 ], transforming growth factor beta-induced (TGFBI) [ 177 ], osteopontin (OPN) [ 178 , 179 ], POSTN [ 180 , 181 ], laminins [ 174 , 182 , 183 ], and tenascin C (TNC) [ 172 , 174 , 184 ].…”
Section: The Tumor Microenvironment and The Breast Cancer Stem Celmentioning
confidence: 99%
“…TGFBI, a POSTN paralog, is a 683 aminoacid ECM protein, which contains a secretory signal sequence, an N-terminal cysteine-rich domain (EMI), four fasciclin-1 (FAS1) domains, and an RGD (Arg-Gly-Asp) integrin binding site at the C-terminal end. We have recently identified TGFBI as a novel prognostic factor in BC and a crucial player in modulating interactions between tumor cells and the microenvironment: depletion of TGFBI reduces tumor hypoxia and normalizes the vasculature, thus dramatically decreasing CSC numbers and ultimately impairing metastasis formation [ 177 ]. The matricellular phosphoglycoprotein OPN has been shown to trigger the tumorsphere formation of ALDH high CD44 + CD24 − BC cells and to boost their metastatic behavior through the interaction with CD44 and RGD-dependent cell surface integrins [ 205 ].…”
Section: The Tumor Microenvironment and The Breast Cancer Stem Celmentioning
confidence: 99%